Q: What is the answer to 12x plus 6-8x-4x-3 plus 12?

Write your answer...

Submit

Related questions

It is x^2 + 12x or x(x + 12).

9x + 2 = 12x + 14 -3x = 12 x = -4

-5 + 12x = 18x + 7Subtract 7 from each side:-12 + 12x = 18xSubtract 12x from each side:-12 = 6xDivide each side by 6:-2 = x

-12x+5x= x(-12+5)= x(-7)= -7x

4x2 is 8+ 12x + 3 collect like terms, 8+3= 11, 12x+11 to solve for x, transpose the 11 to the other side of the = sign, 12x=-11, divide by 12, x=-11/12

2x + 6x + 4x = 12x

1/2 + 5/6 + 2/3 + 3/12 = x 12(1/2 + 5/6 + 2/3 + 3/12 = x) 6 + 10 + 8 + 3 = 12x 16 + 11 = 12x 25 = 12x 25/12

12x-4y+9z+2y =12x-2y+9z

12x - 8 = 10x + 42x = 12x = 6

x2 + 12x - 11 = x2 + 12x + (12/2)2 - (12/2)2 - 11 = (x + 6)2 - 47

Factor. X^2 + 12X X(X + 12) = 0 X = 0 ------------- X + 12 = 0 X = - 12 --------------

12x + 17 = 7 Subtract 17 from both sides: 12x = -10 Divide both sides by 12: x = -10/12 = -5/6

12x+15p-6p+11x = 12x+11x+15p-6p = (12+11)x+(15-6)p = 23x + 9p

If this is algebra then; 3x plus 12x = 15x

12x^2+24x+12 12(x^2+2x+1) 12(x+1)^2

12x+x = 13x

The expression (12x + 36)/48x can be simplified by factoring out 12/12 from the expressions. This leaves (x + 3)/4x.

Think of this a 12 x-rays + 5 x-rays Makes 17 x-rays. 12x+5x=17x

3x multiplied by (12x plus 9) is:3x(12x + 9)= (3x * 12x) + (3x * 9)= 36x2 + 27x

whats the answer for -2x^3+2^2+12x

12x^3+17x^2+5x=0x(12x^2+17x+5)=0x(x+1)(12x+5)=0x=0x=-1x=-5/12

Factor 2x plus 12x plus 28 is (x - 3)(x - 9)

3x2 + 12x = - 1 ie 3x2 + 12x + 1 = 0 has no rational roots. The irrational roots are [-12 +/- sqrt(132)]/6 = -3.915 and -0.085

10+12x=-14 -14-10=12x 12x=-24 x=-2

x2+12x+5 = 3 x2+12x+5-3 = 0 x2+12x+2 = 0